Charitable choice as neoliberal social welfare strategy - Weiss, Robert P. (Social justice, 2001)
Part of a special issue on welfare and punishment in the era of President George W. Bush. Faith-based legislation has been greeted with considerable apprehension by civil libertarians, because despite the innocent appearance of the legislation, it has the potential for great social harm. Charitable choice would allow faith-based welfare organizations to compete for federal contracts and vouchers from various government departments to pay for social programs including child welfare, crime prevention, job training, and hunger relief. Charitable choice is a clever political maneuver by conservative Republicans to capture more Latino, Asian, and African American votes. It actually represents the triumph of neoliberalism in domestic policy as part of an effort to unbridle market forces and free government of its remaining responsibility for social justice.